A method for preparing a near space solar soft bladder material
Flexible thermally conductive nanosheets were prepared by treating hexagonal boron nitride and co-condensation reaction. By combining mechanical shear force and thermal imidization reaction during the coating process, the problems of heat dissipation, structural fragility and coating peeling of near-space solar soft capsule materials under extreme environments were solved, achieving efficient heat dissipation and structural strengthening.
Patent Information
- Application Number
- CN202610412516.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-31
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-03-31
AI Technical Summary
Existing near-space solar soft capsule materials exhibit problems such as insufficient heat dissipation, structural fragility, poor interfacial bonding, and easy peeling of protective coatings under extreme environments.
Flexible thermally conductive nanosheets with terminal isocyanate groups were prepared by liquid-phase exfoliation and surface hydroxylation of hexagonal boron nitride. These nanosheets were then co-condensed with fluorinated octaamino polyhedral oligomeric silsesquioxane and liquid crystal phase aromatic diamine monomers in a polar aprotic solvent to generate a special polyamic acid varnish. Subsequently, during the coating process, a cross-linked network structure was formed by mechanical shearing force and thermal imidization reaction, realizing the microscopic self-assembly of the multifunctional grafted precursor.
It improves the material's thermal conductivity, structural strength, and interfacial bonding, and the protective coating is not easy to peel off, making it suitable for harsh conditions in extreme environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of special polymer composite materials, specifically a method for preparing a near-space solar energy soft capsule material. Background Technology
[0002] Near-space solar soft capsule materials are special composite materials used in harsh environments such as strong sunlight, high waste heat, high concentration of atomic oxygen ablation, and extreme high and low temperature alternation. These materials need to maintain excellent structural integrity during continuous folding and stretching. Therefore, special composite films are recognized as good capsule materials, but conventional processes still have many shortcomings. Modification and composite structure design are effective ways to improve the performance of the matrix, addressing the deficiencies of existing materials. Conventional physical blending of thermally conductive fillers leads to a significant decrease in the matrix's elongation at break and tear strength, while the hard inorganic coating on the surface is inherently brittle and easily develops microcracks and falls off during repeated folding. Currently, the common method for preparing such high-performance composite materials is in-situ graft polymerization combined with roll-to-roll coating. By introducing polyhedral oligomeric silsesquioxane nodes into the polymer network and chemically grafting them with modified thermally conductive nanosheets, and using mechanical shear force to guide microscopic self-assembly, both the mechanical properties and extreme environmental tolerance of the material can be considered. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing near-space solar energy soft capsule materials, so as to improve the overall performance of existing materials in extreme environments. Specifically, the technical solution of this invention is as follows: A method for preparing a near-space solar energy soft capsule material includes the following steps: S1, hexagonal boron nitride is liquid-phase exfoliated and surface-hydroxylated to obtain hydroxylated hexagonal boron nitride; 3-isocyanate-propyltriethoxysilane is used to react with the hydroxylated hexagonal boron nitride to produce flexible thermally conductive nanosheets with isocyanate groups at the ends. Furthermore, in step S1, the conditions for the silanization reaction are: reflux reaction at 80°C for 12 hours in an anhydrous solvent; S2, in a polar aprotic solvent, a fluorinated octaamino polyhedral oligomeric silsesquioxane, a liquid crystal phase aromatic diamine monomer, a fluorinated dianhydride, and a flexible diamine are mixed and subjected to a co-condensation reaction to produce a special polyamic acid varnish; wherein, the total amino to total anhydride functional group equivalent ratio is 1:1, and the amino equivalent of the fluorinated octaamino polyhedral oligomeric silsesquioxane accounts for 0.5% to 2.0% of the total amino equivalent; Furthermore, in step S2, the conditions for the copolymerization reaction are: reacting at 0°C to 5°C for 24 hours; S3, the flexible thermally conductive nanosheets are added to the special polyamic acid varnish for in-situ grafting synthesis to prepare a multifunctional grafted precursor; wherein, the ratio of the molar number of hexagonal boron nitride based on BN basic structural units to the molar number of fluorinated dianhydride in the flexible thermally conductive nanosheets finally obtained in step S1 is 0.4:1 to 1:1. Furthermore, in step S3, during the in-situ grafting synthesis, the grafting temperature is controlled below 25°C to allow the isocyanate groups to react with the carboxyl groups, amide bonds, or terminal amino groups of the special polyamic acid backbone. S4, using the multifunctional grafted precursor as the outer functional coating liquid, a coating composite process is adopted, and thermal imidization is triggered by step temperature increase, and finally cured to obtain the near-space solar soft capsule material.
[0004] Further, in step S4, when using the coating composite process, the coating speed is controlled to be 1-5 m / min and the coating gap to be 50-150 μm, so that a mechanical shear rate of 10-100 s⁻¹ is generated during the coating process; during the step-heating-triggered thermal imidization process, under the guidance of the mechanical shear force during the coating process, the flexible thermally conductive nanosheets are initially self-assembled into a highly parallel stacked structure on the surface of the film; then, the closed-loop dehydration is transformed into a cross-linked network structure, locking the polyhedral oligomeric silsesquioxane and the flexible thermally conductive nanosheets within it; and combined with the orientation of the liquid crystal micro-regions during thermosetting, it is synergistically guided.
[0005] Further, in step S2, the fluorinated dianhydride is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride; the flexible diamine is 4,4'-diaminodiphenyl ether or 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0006] Further, in step S2, the polar aprotic solvent is N,N-dimethylacetamide.
[0007] Further, in step S4, the coating composite process is specifically a roll-to-roll coating composite process; the soft capsule substrate includes an air barrier layer and a load-bearing layer from the inside to the outside, and the multifunctional grafted precursor is coated on the outer surface of the load-bearing layer as an outer protective layer.
[0008] Furthermore, the load-bearing layer is made of high-strength polyaramid fiber woven fabric.
[0009] Furthermore, in step S4, the specific process control conditions for the stepped heating treatment are as follows: sequentially holding at 80℃, 150℃, 250℃, and 320℃ for 1 hour each.
[0010] Compared with the prior art, the present invention has the following improvements and advantages: 1. This invention prepares flexible thermally conductive nanosheets with isocyanate groups at the ends by liquid-phase exfoliation and surface hydroxylation of hexagonal boron nitride, followed by silanization reaction. This technical feature enables the final solidified near-space solar soft capsule material to have excellent thermal conductivity, which can effectively meet the heat dissipation requirements of near-space solar soft capsule material in extreme environments. 2. This invention utilizes a polar aprotic solvent to stir and mix fluorinated octaamino polyhedral oligomeric silsesquioxane, liquid crystal phase aromatic diamine monomer, fluorinated dianhydride, and flexible diamine, and then undergo a co-condensation reaction; this produces a special polyamic acid varnish containing polyhedral oligomeric silsesquioxane nodes and liquid crystal segments, whose special framework design provides a strong and tough microstructure basis for thin film materials; 3. In this invention, the multifunctional grafted precursor is subjected to a stepwise heating process to trigger a thermal imidization reaction, which causes it to undergo a closed-loop dehydration reaction and transform into a cross-linked network structure. This cross-linked network can firmly lock the polyhedral oligomeric silsesquioxane and flexible thermally conductive nanosheets in the system, significantly enhancing the interfacial bonding force between the components, thereby avoiding the loss or aggregation of effective components during long-term use. 4. This invention utilizes the mechanical shearing force during the coating process combined with the orientation guidance effect of the liquid crystal micro-regions during thermosetting to promote the micro-self-assembly of flexible thermally conductive nanosheets on the surface of the composite film, forming a highly parallel stacked structure. This dense stacking not only maximizes the directional thermal conductivity of the nanosheets, but also improves the density and physical protection performance of the material surface. 5. This invention employs roll-to-roll coating composite processes, using a multifunctional grafted precursor as the outer functional coating liquid, which is directly coated onto the outer surface of the load-bearing layer and the gas barrier layer of the soft capsule substrate; the composite film formed after curing effectively covers and protects the substrate, realizing the integrated combination of the outer functional protective structure and the internal load-bearing and gas barrier structure. Detailed Implementation
[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0012] It should be noted that the fluorinated octaaminopolyhedral oligomeric silsesquioxane in this invention can be prepared by amidation reaction of octaaminophenyl polyhedral oligomeric silsesquioxane with fluorinated acyl chloride, or by commercially available fluorinated POSS amine derivatives; the liquid crystal phase aromatic diamine monomer is a diamine with a rigid rod-like structure, specifically selected from one or more of 4,4'-diaminobiphenyl, p-phenylenediamine, or 2-(4-aminophenyl)-5-aminobenzoxazole; the molar amounts of hexagonal boron nitride involved in the embodiments of this invention refer to the molar amounts calculated based on the basic structural unit of BN.
[0013] Example 1: This embodiment provides a method for preparing a near-space solar energy soft capsule material, including the following steps: S1, 10 moles of hexagonal boron nitride were dispersed in a mixed solvent of isopropanol and deionized water, and ultrasonically exfoliated in liquid phase at 500W for 10 hours. After centrifugation to collect the few-layer boron nitride, a 5 mol / L sodium hydroxide solution and a 30% hydrogen peroxide aqueous solution were added, and the mixture was refluxed at 100℃ for 24 hours. After washing and drying, hydroxylated hexagonal boron nitride was obtained. The hydroxylated hexagonal boron nitride was dispersed in anhydrous toluene, and 3-isocyanate-propyltriethoxysilane was added. The mixture was refluxed at 80℃ for 12 hours, and after centrifugation and washing, flexible thermally conductive nanosheets with isocyanate groups at the ends were prepared. S2, in the polar aprotic solvent N,N-dimethylacetamide, is fed with a total amino functional group to total anhydride functional group equivalent ratio of 1:1 to ensure effective growth of the polymer chain; specifically, 0.05 moles of fluorinated octaamino polyhedral oligomeric silsesquioxane, 4 moles of 4,4'-diaminobiphenyl (as an aromatic diamine monomer of the liquid crystal phase) and 5.8 moles of 4,4'-diaminodiphenyl ether (as a flexible diamine) are added, mixed evenly, and then 10 moles of 4,4'-(hexafluoroisopropylidene) phthalic anhydride are added and stirred. The mixture is reacted at 0°C to 5°C for 24 hours to undergo a co-condensation reaction, generating a special polyamic acid varnish containing polyhedral oligomeric silsesquioxane nodes and liquid crystal segments; S3, the flexible thermally conductive nanosheets with isocyanate groups at the ends prepared in step S1 are added to the special polyamic acid varnish in step S2 for in-situ grafting synthesis. The grafting reaction temperature threshold is strictly controlled to be below 25°C and the reaction time is 4 hours. This threshold setting logic is used to suppress the decarboxylation side reaction between isocyanate and the carboxyl groups of the polyamic acid main chain. When the reaction temperature exceeds 25°C, the decarboxylation reaction rate accelerates and CO2 bubbles are easily generated. If the bubbles remain and solidify in the crosslinked network, they will destroy the structural density of the film, increase phonon scattering, and thus reduce the in-plane thermal conductivity of the composite film. Under these conditions, the isocyanate groups react homogeneously with the residual groups or end groups on the special polyamic acid main chain to form a uniform, bubble-free, multifunctional grafted precursor. S4, using the multifunctional grafted precursor as the outer functional coating liquid, is coated onto the outer surface of the soft capsule substrate, which includes a load-bearing layer and an air-barrier layer, using a roll-to-roll coating composite process. The load-bearing layer is made of high-strength polyaramid fiber woven fabric. The coating speed is controlled at 1–5 m / min, and the coating gap is 50–150 μm, so that a 10–100 s coating time is generated during the coating process. -1The mechanical shear rate was measured; the material was transferred to a heating device for stepwise heating to trigger a thermal imidization reaction. It was then held at 80℃, 150℃, 250℃, and 320℃ for 1 hour each to allow the multifunctional grafted precursor to undergo a closed-loop dehydration reaction and transform into a cross-linked network structure. The polyhedral oligomeric silsesquioxane and flexible thermally conductive nanosheets were locked in the cross-linked network. Simultaneously, under the guidance of the mechanical shear force during coating and the orientation of the liquid crystal micro-regions during thermal curing, the flexible thermally conductive nanosheets were microscopically self-assembled on the surface of the film to form a highly parallel stacked structure. Finally, the material was cured to obtain a near-space solar soft capsule material. This embodiment addresses the scenario where solar cells generate significant waste heat under intense near-space sunlight. By introducing flexible diamine 4,4'-diaminodiphenyl ether and combining it with a crosslinking network of a multifunctional grafted precursor, the material maintains good surface integrity after continuous bending at a curvature radius of 2 mm, making it suitable for environments where the capsule undergoes continuous folding and stretching due to pressure changes. The material prepared in this embodiment exhibits an in-plane thermal conductivity of 5.1 W / m·K and an atomic oxygen ablation rate of 2.9 × 10⁻⁶. -25 cm 3 / atom.
[0014] Example 2: This embodiment provides a method for preparing a near-space solar energy soft capsule material, including the following steps: S1, 12 moles of hexagonal boron nitride were subjected to liquid phase exfoliation and surface hydroxylation treatment to obtain hydroxylated hexagonal boron nitride; then, 3-isocyanate-propyltriethoxysilane was used to react with hydroxylated hexagonal boron nitride to silanize it, and flexible thermally conductive nanosheets with isocyanate groups at the ends were prepared. S2, in N,N-dimethylacetamide as a polar aprotic solvent, is fed with a total amino functional group to total anhydride functional group equivalent ratio of 1:1. 0.05 moles of fluorinated octaaminopolyhedral oligomeric silsesquioxane, 8 moles of liquid crystal phase aromatic diamine monomer, 20 moles of 4,4'-(hexafluoroisopropylidene) phthalic anhydride as a fluorinated dianhydride, and 11.8 moles of 2,2-bis[4-(4-aminophenoxy)phenyl]propane as a flexible diamine are added and stirred to undergo a co-condensation reaction, producing a special polyamic acid varnish containing polyhedral oligomeric silsesquioxane nodes and liquid crystal segments. S3, the flexible thermally conductive nanosheets with isocyanate groups at the ends prepared in step S1 are added to the special polyamic acid varnish in step S2 for in-situ grafting synthesis. The isocyanate groups react with the residual amino, carboxyl or terminal amino groups on the main chain of the special polyamic acid to prepare a multifunctional grafted precursor. S4, using the multifunctional grafted precursor as the outer functional coating liquid, is coated onto the outer surface of the soft capsule substrate, which includes a load-bearing layer and an air-barrier layer, using a roll-to-roll coating composite process. The load-bearing layer is made of high-strength polyaramid fiber woven fabric. The coating speed is controlled at 1–5 m / min, and the coating gap is 50–150 μm, so that a 10–100 s coating time is generated during the coating process. -1 The mechanical shear rate was measured; the material was transferred to a heating device for stepwise heating to trigger a thermal imidization reaction. It was then held at 80℃, 150℃, 250℃, and 320℃ for 1 hour each, causing the multifunctional graft precursor to undergo a closed-loop dehydration reaction and transform into a cross-linked network structure. This locked the polyhedral oligomeric silsesquioxane and flexible thermally conductive nanosheets within the cross-linked network. Simultaneously, under the guidance of mechanical shear force during coating combined with the orientation of liquid crystal micro-regions during thermal curing, the flexible thermally conductive nanosheets underwent micro-self-assembly on the film surface to form a highly parallel stacked structure, resulting in a near-space solar soft capsule material. This embodiment adjusted the ratio of thermally conductive nanosheets to liquid crystal phase aromatic diamine monomers and replaced the flexible monomers with 2,2-bis[4-(4-aminophenoxy)phenyl]propane. The aim was to further verify the stress-buffering effect of the flexible components in the cross-linked network under near-space conditions of high-concentration atomic oxygen ablation and extreme temperature fluctuations. Test results showed that the in-plane thermal conductivity under this configuration increased to 5.4 W / m·K, effectively distributing localized high temperatures, and the atomic oxygen ablation rate was 2.7 × 10⁻⁶. - 25 cm 3 / atom.
[0015] Example 3: This embodiment provides a method for preparing a near-space solar energy soft capsule material, including the following steps: S1, 15 moles of hexagonal boron nitride were subjected to liquid phase exfoliation and surface hydroxylation treatment to obtain hydroxylated hexagonal boron nitride; then, 3-isocyanate-propyltriethoxysilane was used to react with hydroxylated hexagonal boron nitride to silanize the hydroxylated hexagonal boron nitride to prepare flexible thermally conductive nanosheets with isocyanate groups at the ends. S2, in N,N-dimethylacetamide as a polar aprotic solvent, is fed with a total amino functional group to total anhydride functional group equivalent ratio of 1:1. 0.075 moles of fluorinated octaaminopolyhedral oligomeric silsesquioxane, 10 moles of liquid crystal phase aromatic diamine monomer, 20 moles of 4,4'-(hexafluoroisopropylidene) phthalic anhydride as a fluorinated dianhydride, and 9.7 moles of 4,4'-diaminodiphenyl ether as a flexible diamine are stirred and mixed to undergo a co-condensation reaction, producing a special polyamic acid varnish containing polyhedral oligomeric silsesquioxane nodes and liquid crystal segments. S3, the flexible thermally conductive nanosheets with isocyanate groups at the ends prepared in step S1 are added to the special polyamic acid varnish in step S2 for in-situ grafting synthesis. The isocyanate groups react with the residual amino, carboxyl or terminal amino groups on the main chain of the special polyamic acid to prepare a multifunctional grafted precursor. S4. A multifunctional grafted precursor is used as the outer functional coating liquid and coated onto the outer surface of a soft capsule substrate, including a load-bearing layer and an air-barrier layer, using a roll-to-roll coating composite process. The load-bearing layer is made of high-strength polyarylate fiber woven fabric. The coating speed is controlled at 1-5 m / min and the coating gap is 50-150 μm to generate a mechanical shear rate of 10-100 s⁻¹ during the coating process. The substrate is then transferred to a heating device for stepwise heating to trigger a thermal imidization reaction. The substrate is held at 80℃, 150℃, 250℃, and 320℃ for 1 hour each to allow the multifunctional grafted precursor to undergo a closed-loop dehydration reaction and transform into a cross-linked network structure. The polyhedral oligomeric silsesquioxane and flexible thermally conductive nanosheets are locked in the cross-linked network. Simultaneously, under the guidance of the mechanical shear force during the coating process and the orientation of the liquid crystal micro-regions during thermal curing, the flexible thermally conductive nanosheets are microscopically self-assembled on the surface of the film to form a highly parallel stacked structure, thus curing to obtain a near-space solar soft capsule material. This embodiment aims to enhance the resistance to strong ultraviolet radiation by increasing the content of fluorinated octaamino polyhedral oligomeric silsesquioxanes. This molecular-level anchoring mechanism prevents the protective coating from detaching during folding. Testing showed that after undergoing alternating high and low temperatures from -70°C to +150°C, the composite film exhibited no significant decrease in peel strength, a tensile strength retention rate greater than 92%, an in-plane thermal conductivity of 5.8 W / m·K, and an atomic oxygen ablation rate of 2.2 × 10⁻⁶. -25 cm 3 / atom.
[0016] Example 4: This embodiment provides a method for preparing a near-space solar energy soft capsule material, including the following steps: S1, 8 moles of hexagonal boron nitride were subjected to liquid phase exfoliation and surface hydroxylation treatment to obtain hydroxylated hexagonal boron nitride; flexible thermally conductive nanosheets with isocyanate groups at the ends were prepared by silanization reaction of 3-isocyanate-propyltriethoxysilane with hydroxylated hexagonal boron nitride. S2, in N,N-dimethylacetamide as a polar aprotic solvent, is fed with a total amino functional group to total anhydride functional group equivalent ratio of 1:1. 0.025 moles of fluorinated octaaminopolyhedral oligomeric silsesquioxane, 9 moles of liquid crystal phase aromatic diamine monomer, 20 moles of 4,4'-(hexafluoroisopropylidene) phthalic anhydride as a fluorinated dianhydride, and 10.9 moles of 2,2-bis[4-(4-aminophenoxy)phenyl]propane as a flexible diamine are stirred and mixed to undergo a co-condensation reaction, producing a special polyamic acid varnish containing polyhedral oligomeric silsesquioxane nodes and liquid crystal segments. S3, the flexible thermally conductive nanosheets with isocyanate groups at the ends prepared in step S1 are added to the special polyamic acid varnish in step S2 for in-situ grafting synthesis. The isocyanate groups react with the residual amino, carboxyl or terminal amino groups on the main chain of the special polyamic acid to prepare a multifunctional grafted precursor. S4. A multifunctional grafted precursor is used as the outer functional coating liquid and coated onto the outer surface of a soft capsule substrate, including a load-bearing layer and an air-barrier layer, using a roll-to-roll coating composite process. The load-bearing layer is made of high-strength polyarylate fiber woven fabric. The coating speed is controlled at 1-5 m / min and the coating gap is 50-150 μm to generate a mechanical shear rate of 10-100 s⁻¹ during the coating process. The substrate is then transferred to a heating device for stepwise heating to trigger a thermal imidization reaction. The substrate is held at 80℃, 150℃, 250℃, and 320℃ for 1 hour each to allow the multifunctional grafted precursor to undergo a closed-loop dehydration reaction and transform into a cross-linked network structure. The polyhedral oligomeric silsesquioxane and flexible thermally conductive nanosheets are locked in the cross-linked network. Simultaneously, under the guidance of the mechanical shear force during the coating process and the orientation of the liquid crystal micro-regions during thermal curing, the flexible thermally conductive nanosheets are microscopically self-assembled on the surface of the film to form a highly parallel stacked structure, thus curing to obtain a near-space solar soft capsule material. This embodiment uses 0.025 moles of fluorinated octaamino polyhedral oligomeric silsesquioxane and 8 moles of hexagonal boron nitride inorganic functional units to evaluate the retention of tear strength in the matrix material. Due to the chemical grafting effect of the flexible siloxane chains, microphase separation is avoided. In the MIT flexural endurance test, no microcracks were observed under a scanning electron microscope after 100,000 consecutive bends. The in-plane thermal conductivity was 4.9 W / m·K, and the atomic oxygen ablation rate was 2.9 × 10⁻⁶. -25 cm 3 / atom.
[0017] Example 5: This embodiment provides a method for preparing a near-space solar energy soft capsule material, including the following steps: S1, 20 moles of hexagonal boron nitride were subjected to liquid phase exfoliation and surface hydroxylation treatment to obtain hydroxylated hexagonal boron nitride; flexible thermally conductive nanosheets with isocyanate groups at the ends were prepared by silanization reaction of 3-isocyanate-propyltriethoxysilane with hydroxylated hexagonal boron nitride. S2, in N,N-dimethylacetamide as a polar aprotic solvent, is fed with a total amino functional group to total anhydride functional group equivalent ratio of 1:1. 0.1 moles of fluorinated octaamino polyhedral oligomeric silsesquioxane, 12 moles of liquid crystal phase aromatic diamine monomer, 20 moles of 4,4'-(hexafluoroisopropylidene) phthalic anhydride as a fluorinated dianhydride, and 7.6 moles of 4,4'-diaminodiphenyl ether as a flexible diamine are stirred and mixed, and a co-condensation reaction occurs to generate a special polyamic acid varnish containing polyhedral oligomeric silsesquioxane nodes and liquid crystal segments. S3, the flexible thermally conductive nanosheets with isocyanate groups at the ends prepared in step S1 are added to the special polyamic acid varnish in step S2 for in-situ grafting synthesis. The isocyanate groups react with the residual amino, carboxyl or terminal amino groups on the main chain of the special polyamic acid to prepare a multifunctional grafted precursor. S4, using the multifunctional grafted precursor as the outer functional coating liquid, is coated onto the outer surface of the soft capsule substrate, which includes a load-bearing layer and an air-barrier layer, using a roll-to-roll coating composite process. The load-bearing layer is made of high-strength polyaramid fiber woven fabric. The coating speed is controlled at 1–5 m / min, and the coating gap is 50–150 μm, so that a 10–100 s coating time is generated during the coating process. -1 The mechanical shear rate was measured; the material was transferred to a heating device for stepwise heating to trigger a thermal imidization reaction. It was then held at 80℃, 150℃, 250℃, and 320℃ for 1 hour each, causing the multifunctional graft precursor to undergo a closed-loop dehydration reaction and transform into a cross-linked network structure. This locked the polyhedral oligomeric silsesquioxane and flexible thermally conductive nanosheets within the cross-linked network. Simultaneously, under the guidance of mechanical shear force during coating combined with the orientation of liquid crystal micro-regions during thermal curing, the flexible thermally conductive nanosheets underwent micro-self-assembly on the film surface to form a highly parallel stacked structure, resulting in a near-space solar soft capsule material. This embodiment increases the ratio of the liquid crystal phase aromatic diamine monomer and the flexible thermally conductive nanosheet, specifically to verify the enhancing effect of the liquid crystal segment orientation force on the in-plane heat dissipation structure during the coating film formation process; the results show that while extending the gas diffusion path, the in-plane thermal conductivity reaches 6.2 W / m·K, and the atomic oxygen ablation rate is 2.3 × 10⁻⁶. -25 cm 3 / atom, the temperature of the solar cell backsheet is reduced by about 30°C, improving power generation efficiency.
[0018] Comparative Example 1: This comparative example provides a method for preparing a conventional near-space soft capsule material; the difference from Example 1 is that: fluorinated octaamino polyhedral oligomeric silsesquioxane and liquid crystal phase aromatic diamine monomer are not introduced; hexagonal boron nitride is not silanized, but is directly added as a high thermal conductivity filler to the polyimide matrix synthesized from ordinary dianhydride and diamine by physical blending; the remaining coating and curing processes are the same as in Example 1. This comparative example illustrates the effect of physically blended thermally conductive fillers on the properties of the matrix material. Due to the large amount of ungrafted boron nitride, the elongation at break and tear strength of the matrix material are significantly reduced. Furthermore, without mechanical shear orientation guidance, the in-plane thermal conductive network cannot be effectively constructed, and the tested in-plane thermal conductivity is only 1.8 W / m·K.
[0019] Comparative Example 2: This comparative example provides another method for preparing conventional near-space soft capsule materials; the difference from Example 1 is that a layer of silicon dioxide anti-atomic oxide coating is magnetron sputtered on the surface of a flexible polyimide film, and no multifunctional grafted precursor is prepared. This was used to compare the failure risk of inorganic coatings with high intrinsic hardness during biasing and folding processes. After bending cycle testing, the surface showed that microcracks and peeling occurred early due to high brittleness, failing to meet the requirement that the protective structure would not fall off after tens of thousands of folds.
[0020] Experimental results comparison: The following is a comparison table of key performance indicators between the examples and comparative examples, mainly examining in-plane thermal conductivity, atomic oxygen erosion rate, and tensile strength retention: Note: In the table above, Comparative Example 2 suffered severe peeling of the anti-atomic coating after bending, resulting in a sharp increase in its atomic oxygen erosion rate, making it impossible to determine an effective stable value. Furthermore, due to the severe peeling and failure of the surface coating, its 75% tensile strength retention rate only represents the mechanical baseline of the internal polyarylate load-bearing layer substrate itself. As can be seen from the above comparative data, the embodiments of the present invention have a synergistic improvement effect on in-plane thermal conductivity and tensile strength retention rate. Among them, embodiment 5 has the best in-plane thermal conductivity under the guidance of the film structure. The physical doping or hard coating methods in the comparative examples all face technical obstacles such as mechanical decay or coating peeling.
[0021] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a near-space solar energy soft capsule material, characterized in that, Includes the following steps: S1, hexagonal boron nitride is liquid-phase exfoliated and surface-hydroxylated to obtain hydroxylated hexagonal boron nitride; 3-isocyanate-propyltriethoxysilane is used to react with the hydroxylated hexagonal boron nitride to produce flexible thermally conductive nanosheets with isocyanate groups at the ends. S2, in a polar aprotic solvent, a fluorinated octaamino polyhedral oligomeric silsesquioxane, a liquid crystal phase aromatic diamine monomer, a fluorinated dianhydride, and a flexible diamine are mixed and subjected to a co-condensation reaction to produce a special polyamic acid varnish; wherein, the total amino to total anhydride functional group equivalent ratio is 1:1, and the amino equivalent of the fluorinated octaamino polyhedral oligomeric silsesquioxane accounts for 0.5% to 2.0% of the total amino equivalent; the flexible diamine is 4,4'-diaminodiphenyl ether or 2,2-bis[4-(4-aminophenoxy)phenyl]propane; S3, the flexible thermally conductive nanosheets are added to the special polyamic acid varnish for in-situ grafting synthesis to prepare a multifunctional grafted precursor; wherein, the molar ratio of hexagonal boron nitride based on BN basic structural units to the molar ratio of fluorinated dianhydride in the flexible thermally conductive nanosheets finally obtained in step S1 is 0.4:1 to 1:1; during the in-situ grafting synthesis process, the grafting temperature is controlled below 25°C to allow the isocyanate groups to react with the carboxyl groups, amide bonds or terminal amino groups of the special polyamic acid main chain; S4, using the multifunctional grafted precursor as the outer functional coating liquid, a coating composite process is employed, with thermal imidization triggered by stepped temperature increases, ultimately curing to obtain the near-space solar soft capsule material; wherein, during the coating composite process, the coating speed is controlled at 1–5 m / min, the coating gap is 50–150 μm, and a coating time of 10–100 s is generated during the coating process. -1 The mechanical shear rate; the specific process control conditions for the stepped heating treatment are: sequentially holding at 80℃, 150℃, 250℃, and 320℃ for 1 hour each.
2. The method for preparing a near-space solar energy soft capsule material according to claim 1, characterized in that, In step S2, the fluorinated dianhydride is 4,4'-(hexafluoroisopropylidene) phthalic anhydride.
3. The method for preparing a near-space solar energy soft capsule material according to claim 1, characterized in that, In step S2, the polar aprotic solvent is N,N-dimethylacetamide.
4. The method for preparing a near-space solar energy soft capsule material according to claim 1, characterized in that, In step S4, the coating composite process is specifically a roll-to-roll coating composite process; the soft capsule material includes an air barrier layer and a load-bearing layer from the inside to the outside, and the multifunctional grafted precursor is coated on the outer surface of the load-bearing layer as an outer protective layer.
5. The method for preparing a near-space solar energy soft capsule material according to claim 4, characterized in that, The load-bearing layer is made of high-strength polyarylate fiber woven fabric.
Citation Information
Patent Citations
Polyimide film and preparation method thereof
CN105461923A
Polyhedral oligomeric silsesquioxane-polyamic acid polymer resistant to plasma etching and preparation method thereof
CN110229332A
High-thermal-conductivity modified hexagonal boron nitride / waterborne polyimide composite material
CN114181529A
Preparation method of h-BN / PI high-temperature-resistant anticorrosive coating
CN121086658A
